HAHUNENG: AN ANTHROPOLOGICAL STUDY BASED ON CONTEXTUAL THEOLOGY ON COMMUNITY SOCIAL COOPERATION IN HUTUMURI-MALUKU - Resa Dandirwalu; Pieter Walter Souhuwat (International Journal of Education, Information Technology, and Others, 2020)
This research examines the Hutumuri congregation's understanding of Hahuneng, with the aim of analyzing the congregation's understanding of Hahuneng, then the method used is theological research method, with the following steps: first, conducting qualitative research and using interviews as a data collection technique, and analyzing, and the process of interpretation and communication of values ​​and contexts in the life of a congregation and conducting theological normative evaluations using contextual theology anthropological models, because they are centered on the values ​​and goodness of human culture. The result obtained is that Hahuneng is understood by the Hutumuri congregation/community as a fellowship, because togetherness between soa in the Hutumuri Country, becomes an important value for the creation of social harmony in the GPM Hutumuri Congregation, so that life is always colored with harmony, peace and mutual respect. and are willing to work together for the common good over the interests of soa; respect for Upu Ila Kahuresi and the spirits of the dead / ancestors, respect for the ancestors are values ​​that are of great concern and must be a force that is firmly planted in the personality of each Congregation; and third, sacredness. Sacredness is always associated with beliefs in the unseen, mystical, supernatural, and made the norm together as moral values.